EFEKTIVITAS SELF ASSESSMENT PADA TUTORIAL PROBLEM BASED LEARNING DI FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - ARMAN MAULANA; DESI ISNAYANTI (JURNAL ILMIAH KOHESI, 2021)
Self-assessment of abilities in the learning process has the benefit of knowing one's own strengths and weaknesses. Thisstudy aims to determine the effectiveness of self assessment on PBL (problem based learning) tutorials. The PBL Tutorial isa Small Group Discussion that studies about existing disease problems. Method: this research method is an experimentalmethod. Sampling was done by total sampling and divided into intervention groups and control groups. The results showedthat there were significant differences in the pretest and posttest scores in the intervention and control groups, in the averagevalue of the intervention and control group tutorials with significance, in the posttest scores between the two groups with pvalues <0.05. Thus there is the effectiveness of self assessment in the PBL tutorial. The results of self assessment aregood if students know the weaknesses and strengths in the learning process. Self assessment succeeded in increasingstudent learning motivation so that it showed satisfying student learning achievements.